New insights into the sensing mechanism of shape controlled ZnO particles. Issue 58 (31st May 2016) - D'Arienzo, Massimiliano; Redaelli, Matteo; Di Credico, Barbara; Polizzi, Stefano; Scotti, Roberto; Morazzoni, Franca
Abstract : Monitoring the sensing behavior and the reactivity of ESR active VO˙ species in ZnO crystals with specific exposed surfaces and in nanoparticles with uneven shape, different morphology-dependent sensing mechanism have been identified. Abstract : The sensing behavior of pyramidal (PY), prismatic hexagonal (EP) and hexagonal rod-like (ER) ZnO micro and sub-microparticles, has been compared with that of commercial ZnO (ZnO®) particles having nanometric size and uneven shape. The performances have been firstly related to the predominance of specific crystal surfaces and then, more in depth, to the paramagnetic defects in ZnO ( and ), detected by Electron Spin Resonance (ESR), in order to associate the particles morphology with the defects amount and reactivity and, in turn, with a particular sensing mechanism. The results showed that the sensing behavior of ZnO® containing irregular nanoparticles is essentially related to the alternate formation and filling of oxygen vacancies during the gas pulse (oxygen vacancy mechanism), while that of ER and EP crystals does not seem to directly involve the defects. In particular, the sensing properties of shape controlled ZnO particles are mainly attributed to the ability of (0001) exposed surfaces in favoring a far better chemisorption of negatively charged oxygen species, then available for the reactions with the reducing gas ( i.e. ionosorption mechanism). The outcomes and the approach adopted in this study may positively contribute to the debate still existing between the oxygen vacancy and ionosorption models by giving indications on the predominance of a specific sensing mechanism in shape controlled ZnO.